Composite nanofiber elastic adhesive bandage and method of making same
Patent Information
- Application Number
- CN202611240335.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
静电纺丝纳米纤维由于纤维内部组分取向性差、界面相互作用弱以及纤维之间接触微弱等因素,其力学性能和抗疲劳性能普遍较弱
[0026] 1. In the polyrotaxane slip ring elastomer-reinforced breathable layer, α-cyclodextrin cyclic molecules are interwoven with polyethylene glycol polymer chains to form slip ring structures, allowing the cyclic molecules to slide along the polymer chains. Under external force, the cyclic molecules in the polyrotaxane slide along the polymer chains, effectively dispersing concentrated stress and improving the material's fracture strength. This molecular-scale slip ring sliding energy dissipation mechanism, together with the mesoscale fold unfolding-recovery mechanism of the double-folded structure, forms a cross-scale synergy. During small deformations, the polyrotaxane slip ring effect bears the load, while during large deformations, the double-folded structure unfolds and adapts, with both achieving high elastic response across the entire deformation domain. Simultaneously, the polyrotaxane slip ring effect also solves the delamination problem of existing multilayer structures under repeated stretching by uniformly dispersing interlaminar stress.
Smart Images

Figure CN122912164A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of bandages, and more specifically, to composite nanofiber elastic adhesive bandages and their preparation methods. Background Technology
[0002] Bandages are the most basic wound covering and fixation materials in clinical surgery and emergency care. Their main functions include protecting the wound surface, absorbing exudate, isolating external contaminants, and providing physical support for injured tissues. With the development of materials science and medical textile technology, elastic adhesive bandages have gradually become a research hotspot. These bandages, based on traditional bandaging functions, introduce an elastic substrate and adhesive layer to achieve dynamic fit and fixation of moving parts such as joints, preventing slippage or displacement during use. However, existing elastic adhesive bandages are mostly textile-based elastic bandages or coated elastic tapes, which have limited elastic deformation capabilities. The adhesive layer is prone to failure in humid environments, making it difficult to simultaneously meet the comprehensive requirements of high elastic deformation, long-lasting adhesion, and good breathability.
[0003] In recent years, electrospinning technology has been gradually introduced into the fields of bandages and wound dressings due to its advantages in preparing nanofibers with high porosity and large specific surface area. Nanofiber membranes constructed using electrospinning technology have a microstructure similar to the extracellular matrix, exhibiting good breathability and biocompatibility. Based on this, Chinese patent CN201911197939.0 discloses a composite nanofiber elastic bandage and its preparation method. This bandage is made using an electrospinning device with a double-layer elastic membrane as the collecting electrode. It features a three-layer composite nanofiber membrane with a double-fold structure, including an absorbent layer, a drug-loaded layer, and a protective layer stacked from bottom to top. This bandage utilizes the double-fold structure to achieve good elasticity, allowing it to expand and contract with the joint during joint movement, avoiding restriction of joint movement at the injured site and bandage displacement.
[0004] However, the existing composite nanofiber elastic bandages still have significant shortcomings in terms of elasticity. Specifically, the elasticity of these bandages mainly comes from the passive stretching of the double-pleated structure, meaning that the pleats unfold to provide deformation capacity when subjected to external stretching, but they lack active contraction capacity. More importantly, existing technologies do not address the fatigue resistance of the bandages under repeated stretch-recovery cycles. Electrospun nanofibers generally have weak mechanical properties and fatigue resistance due to poor orientation of internal fiber components, weak interfacial interactions, and weak contact between fibers. In daily activities at joints, bandages need to undergo hundreds or thousands of stretch-recovery cycles. Under long-term cyclic loading, the existing double-pleated structure is prone to irreversible damage to the pleats and a decrease in elastic recovery rate. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a composite nanofiber elastic adhesive bandage and its preparation method.
[0006] The specific technical solution is as follows: a composite nanofiber elastic adhesive bandage, comprising, from bottom to top, the following layers stacked sequentially: a metal-phenolic network modified Janus wetting gradient adhesive layer; a drug-loaded layer doped with MXene two-dimensional nanosheets; a liquid metal-elastomer composite piezoelectric elastic layer; and a polyrotaxane slip ring elastomer-reinforced breathable layer.
[0007] In a further preferred embodiment, the phenolic ligand in the metal-phenolic network is tannic acid or gallic acid, and the metal ion in the metal-phenolic network is Fe. 3+ or Cu 2+ The molar ratio of phenolic ligands to metal ions is 1-3:1; the doping mass of the metal-phenolic network in the metal-phenolic network modified Janus wetting gradient adhesion layer is 2-10 wt%.
[0008] In a further preferred embodiment, the liquid metal is a eutectic gallium-indium alloy, wherein the gallium content is 75-76 wt% and the indium content is 24-25 wt%; the liquid metal nanodroplets have a particle size of 50-200 nm, and after surface ligand modification, the liquid metal nanodroplets are dispersed in the piezoelectric polymer matrix constituting the liquid metal-elastomer composite piezoelectric elastic layer; the mass percentage of the liquid metal nanodroplets in the fiber formed by the composite piezoelectric elastic layer is 1-10 wt%.
[0009] In a further preferred embodiment, the polyrotaxane is formed by α-cyclodextrin cyclic molecules threaded onto a polyethylene glycol polymer chain; wherein the molar ratio of α-cyclodextrin to the ethylene glycol repeating unit in the polyethylene glycol chain is 1:2-4; and the blending mass percentage of polyrotaxane in the polyrotaxane slip ring elastomer reinforced breathable layer is 5-20 wt%.
[0010] Another object of the present invention is to provide a method for preparing a composite nanofiber elastic adhesive bandage, comprising the following steps:
[0011] Step 1: Preparation of spinning solution
[0012] A metal-phenolic network modified Janus hydrophilic layer spinning solution A was prepared by dissolving hydrophilic polymer materials, phenolic ligands, and metal ions in a solvent; a Janus hydrophobic layer spinning solution B was prepared by dissolving hydrophobic polymer materials in a solvent; a drug-loaded layer spinning solution C was prepared by mixing and dispersing hydrophilic polymer materials and MXene nanosheets in a solvent; a liquid metal-piezoelectric elastic layer spinning solution D was prepared by mixing and dispersing liquid metal nanodroplets, piezoelectric polymers, and elastic polymers in a solvent; and a polyrotaxane breathable layer spinning solution E was prepared by mixing polyrotaxane slip ring elastomers and thermoplastic elastomers in a solvent.
[0013] Step 2: Setting up the electrospinning device
[0014] The electrospinning device includes a high-voltage power supply, a liquid supply mechanism, a spinning nozzle, and a collecting electrode. The collecting electrode includes a conductive layer, a first elastic membrane, and a second elastic membrane stacked sequentially from bottom to top. Both the first and second elastic membranes are insulating materials and are under tension. The tension of the first elastic membrane is greater than that of the second elastic membrane. Multiple strip-shaped grooves are uniformly arranged on the first elastic membrane along its tension direction. Circular through holes are uniformly distributed on the second elastic membrane.
[0015] Step 3: Electrospun metal-phenolic network modified Janus wetting gradient adhesion layer
[0016] The metal-phenolic network modified Janus hydrophilic layer spinning solution A is injected into the liquid supply mechanism, and the metal-phenolic network modified hydrophilic inner layer is electrospun on the second elastic membrane; then switch to the Janus hydrophobic layer spinning solution B, and directly electrospun the hydrophobic outer layer on the hydrophilic inner layer to form an electrospun metal-phenolic network modified Janus wetting gradient adhesion layer.
[0017] Step 4: Electrospinning the drug-loaded layer
[0018] The drug-coating solution C is injected into the supply mechanism, and a nanofiber film doped with MXene nanosheets is directly electrospun on the surface of the metal-phenolic network modified Janus wetting gradient adhesion layer as a drug-carrying layer.
[0019] Step 5: Electrospinning liquid metal-piezoelectric elastic layer
[0020] The liquid metal-piezoelectric elastic layer spinning solution D is injected into the liquid supply mechanism, and a layer of liquid metal nanodroplets, piezoelectric polymer and elastic polymer composite nanofiber film is directly electrospun on the upper surface of the drug-loaded layer as the liquid metal-piezoelectric elastic layer, and the liquid metal-piezoelectric elastic layer is polarized.
[0021] Step 6: Electrospun polyrotaxane breathable layer
[0022] The polyrotaxane permeable layer spinning solution E is injected into the liquid supply mechanism, and a polyrotaxane slip ring elastomer and thermoplastic elastomer composite nanofiber membrane is directly electrospun on the upper surface of the liquid metal-piezoelectric elastic layer as the polyrotaxane permeable layer.
[0023] Step 7: Take the membrane
[0024] The second elastic membrane and the first elastic membrane are restored to their original lengths, and the resulting multilayer composite nanofiber membrane shrinks to form a double-folded structure. The multilayer composite nanofiber membrane is then removed from the second elastic membrane to obtain the composite nanofiber elastic adhesive bandage.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] 1. In the polyrotaxane slip ring elastomer-reinforced breathable layer, α-cyclodextrin cyclic molecules are interwoven with polyethylene glycol polymer chains to form slip ring structures, allowing the cyclic molecules to slide along the polymer chains. Under external force, the cyclic molecules in the polyrotaxane slide along the polymer chains, effectively dispersing concentrated stress and improving the material's fracture strength. This molecular-scale slip ring sliding energy dissipation mechanism, together with the mesoscale fold unfolding-recovery mechanism of the double-folded structure, forms a cross-scale synergy. During small deformations, the polyrotaxane slip ring effect bears the load, while during large deformations, the double-folded structure unfolds and adapts, with both achieving high elastic response across the entire deformation domain. Simultaneously, the polyrotaxane slip ring effect also solves the delamination problem of existing multilayer structures under repeated stretching by uniformly dispersing interlaminar stress.
[0027] 2. Eutectic gallium-indium alloy nanodroplets are dispersed in a piezoelectric polymer matrix. When microcracks occur in the nanofibers, the liquid metal droplets can flow and fill the cracks due to their room-temperature liquid properties. This microscale (nano-micron) self-healing mechanism complements the self-healing mechanism of polyrotaxane slip ring elastomers at the molecular scale, which is achieved by the reintroduction of cyclic molecules into the polymer chain. The combination of molecular-scale chemical and supramolecular self-healing with mesoscale physical flow filling constructs a cross-scale self-healing network, extending the service life and reliability of the bandage.
[0028] 3. When liquid metal nanodroplets are stretched, they de-adhede at the interface, forming additional nanoscale pores. Combined with the unfolding of the double-pleated structure, the breathability of the bandage increases by 35% when stretched by 50%, achieving an intelligent response of enhanced breathability for sports and overturning the technical prejudice that stretching traditional bandages will block breathability.
[0029] 4. In the inner layer of the metal-phenolic network modified Janus wetting gradient adhesion layer, tannic acid (or gallic acid) and Fe... 3+ (or Cu) 2+ Coordination self-assembly forms a metal-phenolic network; the catechol / gallic acid groups in the metal-phenolic network have universal adhesive properties and can bind to proteins on the skin surface through multi-point non-covalent interactions such as hydrogen bonding, hydrophobic interaction and metal coordination; unlike traditional adhesives whose adhesion decreases sharply in a wet environment, the catechol groups of the metal-phenolic network form more hydrogen bonds and coordination bonds with proteins on the skin surface in a wet environment, and the wet adhesion is actually enhanced;
[0030] 5. The Janus wetting gradient adhesive layer has asymmetric wetting properties, with an inner contact angle of less than 60 degrees (hydrophilic) and an outer contact angle of greater than 130 degrees (hydrophobic). It utilizes differential capillary effect to achieve unidirectional pumping of sweat and exudate from the skin side to the outside. The hydrophilic properties of the catechol groups in the metal-phenolic network further enhance the hydrophilic driving force of the inner layer, increasing the unidirectional liquid transport rate. At the same time, the unidirectional moisture-wicking function of the Janus structure continuously removes moisture from the skin-bandage interface, keeping the metal-phenolic network adhesive layer in optimal contact with the skin. Moisture is removed in time, and the catechol groups of the M metal-phenolic network can directly contact the skin surface proteins to form strong adhesion. The moisture-wicking function promotes adhesion, and the adhesive layer maintains the patency of the moisture-wicking channels, forming a positive feedback loop.
[0031] 6. Ti3C2T doped in the drug-loaded layer X MXene nanosheets, with a diameter of 200 nm-2 μm and a thickness of 1-5 nm, have a two-dimensional sheet structure. Unlike traditional zero-dimensional nanoparticles (such as nano-silver and nano-silica) that easily clog the pores between fibers, the two-dimensional sheet structure of MXene forms surface-to-point contact in nanofibers, which does not block the gas transport channels between fibers. On the contrary, MXene nanosheets form gas sliding channels on the fiber surface, allowing water vapor molecules to pass through the fiber membrane with lower resistance.
[0032] 7. MXene Ti3C2T X With excellent photothermal conversion efficiency, MXene nanosheets efficiently convert light energy into heat energy under near-infrared light irradiation, generating local high temperature and physically killing bacteria through thermal effect; unlike traditional antibiotics or metal ion antibacterial agents, MXene's photothermal antibacterial mechanism is a physical bactericidal mechanism that does not rely on drug release or reactive oxygen species generation, and therefore will not induce bacteria to develop drug resistance.
[0033] 8. The metal-phenolic network itself has broad-spectrum antibacterial activity (by disrupting bacterial cell membranes and generating reactive oxygen species), which, together with the photothermal antibacterial properties of MXene, forms a dual antibacterial barrier of chemical and physical antibacterial properties, achieving synergistic antibacterial action without antibiotics or drug resistance.
[0034] 9. The wet adhesion function of the metal-phenolic network, the one-way moisture conduction function of the Janus wetting gradient adhesion layer, the photothermal antibacterial function of MXene, and the on-demand thermotherapy function of liquid metal form a four-fold linkage mechanism of "adhesion, moisture conduction, antibacterial and thermotherapy"; the metal-phenolic network firmly adheres the bandage to the moist wound, the Janus layer continuously drains the wound exudate outward, MXene sterilizes under light when flowing through the drug-loaded layer, the liquid metal generates Joule heating under the alternating magnetic field to promote tissue regeneration, and polyrotaxane ensures the elastic recovery of the bandage. Attached Figure Description
[0035] Figure 1 Line graphs showing the maximum tensile strength, recovery rate after 100 cycles, recovery rate after 500 cycles, and recovery rate after 1000 cycles for control group 1, control group 2, experimental group 1, and experimental group 2.
[0036] Figure 2 A bar chart showing the water vapor transmission rate of control group 1, control group 2, experimental group 1, and experimental group 2;
[0037] Figure 3 A bar chart showing the static air permeability of control group 1, control group 2, experimental group 1, and experimental group 2;
[0038] Figure 4 The graph shows the statistical line graphs of dry peel strength, wet peel strength, wet and dry retention rates for control group 1, control group 2, experimental group 1, and experimental group 2. Detailed Implementation
[0039] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0040] Example 1
[0041] Composite nanofiber elastic adhesive bandage, comprising layers stacked sequentially from bottom to top:
[0042] Metal-phenolic network modified Janus wetting gradient adhesion layer;
[0043] Drug-carrying layer doped with MXene two-dimensional nanosheets;
[0044] Liquid metal-elastomer composite piezoelectric elastic layer;
[0045] Polyrotaxane slip ring elastomer reinforces the breathable layer;
[0046] The metal-phenolic network modified Janus wetting gradient adhesion layer, drug-loaded layer, liquid metal-elastomer composite piezoelectric elastic layer, and polyrotaxane slip ring elastomer reinforced breathable layer all have a double-folded structure. The metal-phenolic network modified Janus wetting gradient adhesion layer has asymmetric wettability, with an inner layer contact angle of less than 60 degrees and an outer layer contact angle of greater than 130 degrees. The inner layer is doped with a metal-phenolic network. The metal-phenolic network of the metal-phenolic network modified Janus wetting gradient adhesion layer is formed by the self-assembly of phenolic ligands and metal ions.
[0047] The liquid metal-elastomer composite piezoelectric elastic layer is made by electrospinning liquid metal nanodroplets and piezoelectric polymer; the polyrotaxane slip ring elastomer reinforced breathable layer is made by electrospinning polyrotaxane slip ring elastomer and thermoplastic elastomer, wherein the polyrotaxane used in the polyrotaxane slip ring elastomer is formed by cyclic molecules threaded onto polymer chains.
[0048] In the polyrotaxane slip ring elastomer-reinforced breathable layer, α-cyclodextrin cyclic molecules are interwoven with polyethylene glycol polymer chains to form slip ring structures, allowing the cyclic molecules to slide along the polymer chains. Under external force, the cyclic molecules in the polyrotaxane slide along the polymer chains, effectively dispersing concentrated stress and improving the material's fracture strength. This molecular-scale slip ring sliding energy dissipation mechanism, together with the mesoscale wrinkle unfolding-recovery mechanism of the double-folded structure, forms a cross-scale synergy. During small deformations, the polyrotaxane slip ring effect bears the burden, while during large deformations, the double-folded structure unfolds and adapts, with both achieving high elastic response across the entire deformation domain. Simultaneously, the polyrotaxane slip ring effect also solves the delamination problem of existing multilayer structures under repeated stretching by uniformly dispersing interlaminar stress.
[0049] Eutectic gallium-indium alloy nanodroplets are dispersed in a piezoelectric polymer matrix. When microcracks occur in the nanofibers, the liquid metal droplets can flow and fill the cracks due to their room-temperature liquid properties. This microscale (nano-micron) self-healing mechanism complements the self-healing mechanism of polyrotaxane slip ring elastomers, which achieves self-healing at the molecular scale by re-entering the polymer chain through cyclic molecules. The combination of molecular-scale chemical and supramolecular self-healing with mesoscale physical flow filling constructs a cross-scale self-healing network, extending the service life and reliability of the bandage.
[0050] When liquid metal nanodroplets are stretched, they de-adhede at the interface, forming additional nanoscale pores. Combined with the unfolding of the double-pleated structure, the air permeability of the bandage increases by 35% when stretched by 50%, achieving an intelligent response of enhanced breathability for sports and overturning the traditional prejudice that stretching a bandage will block breathability.
[0051] Furthermore, the MXene two-dimensional nanosheets are Ti3C2T. X Transition metal carbide nanosheets; Ti3C2T X The transition metal carbide nanosheets have a diameter of 200 nm-2 μm and a thickness of 1-5 nm, with a doping mass of 0.5-5 wt% in the drug-loaded layer; MXene two-dimensional nanosheets generate a photothermal effect under visible or near-infrared light irradiation, and can be used for on-demand antibacterial applications.
[0052] The pulley effect of the polyrotaxane slip ring elastomer and the double-folded structure form a molecular-mesoscopic cross-scale elastic response mechanism; the liquid metal nanodroplets can flow and fill the cracks when the fiber breaks, achieving room temperature self-healing.
[0053] Furthermore, the phenolic ligands in the metal-phenolic network are tannic acid or gallic acid, and the metal ion in the metal-phenolic network is Fe. 3+ or Cu 2+ The molar ratio of phenolic ligands to metal ions is 1-3:1; the doping mass of the metal-phenolic network in the metal-phenolic network modified Janus wetting gradient adhesion layer is 2-10 wt%.
[0054] In the inner layer of the metal-phenolic network modified Janus wetting gradient adhesion layer, tannic acid (or gallic acid) and Fe... 3+ (or Cu) 2+ Coordination self-assembly forms a metal-phenolic network; the catechol / gallic acid groups in the metal-phenolic network have universal adhesive properties and can bind to proteins on the skin surface through multi-point non-covalent interactions such as hydrogen bonding, hydrophobic interaction and metal coordination; unlike traditional adhesives whose adhesion decreases sharply in a wet environment, the catechol groups of the metal-phenolic network form more hydrogen bonds and coordination bonds with proteins on the skin surface in a wet environment, and the wet adhesion is enhanced.
[0055] Furthermore, the liquid metal is a eutectic gallium-indium alloy, in which the gallium content is 75-76 wt% and the indium content is 24-25 wt%; the liquid metal nanodroplets have a particle size of 50-200 nm, and after being modified with surface ligands, the liquid metal nanodroplets are dispersed in the piezoelectric polymer matrix constituting the liquid metal-elastomer composite piezoelectric elastic layer; the mass percentage of the liquid metal nanodroplets in the fiber formed by the composite piezoelectric elastic layer is 1-10 wt%.
[0056] Furthermore, the unidirectional liquid transport rate of the metal-phenolic network modified Janus wetting gradient adhesion layer is not less than 2.0 mL·min. -1 ·cm -2 The metal-phenolic network forms hydrogen bonds and coordination bonds with the skin surface in a humid environment, and the wet peel strength is not less than 5.0 N / cm.
[0057] The wet adhesion function of the metal-phenolic network, the unidirectional moisture conduction function of the Janus wetting gradient adhesion layer, the photothermal antibacterial function of MXene, and the on-demand thermotherapy function of liquid metal form a four-fold tandem treatment mechanism of "adhesion-moisture conduction-antibacterial-thermotherapy".
[0058] Furthermore, the polyrotaxane is formed by α-cyclodextrin cyclic molecules threaded onto a polyethylene glycol polymer chain; wherein the molar ratio of α-cyclodextrin to the ethylene glycol repeating unit in the polyethylene glycol chain is 1:2-4; and the blending mass percentage of polyrotaxane in the polyrotaxane slip ring elastomer reinforced breathable layer is 5-20 wt%.
[0059] The Janus wetting gradient adhesive layer exhibits asymmetric wetting properties, with an inner contact angle of less than 60 degrees (hydrophilic) and an outer contact angle of greater than 130 degrees (hydrophobic). It utilizes differential capillary effect to achieve unidirectional pumping of sweat and exudate from the skin side to the outside. The hydrophilic properties of the catechol groups in the metal-phenolic network further enhance the hydrophilic driving force of the inner layer, increasing the unidirectional liquid transport rate. At the same time, the unidirectional moisture-wicking function of the Janus structure continuously removes moisture from the skin-bandage interface, ensuring that the metal-phenolic network adhesive layer always maintains optimal contact with the skin. Moisture is removed in time, allowing the catechol groups of the M metal-phenolic network to directly contact the skin surface proteins to form strong adhesion. The moisture-wicking function promotes adhesion, and the adhesive layer maintains the patency of the moisture-wicking channels, forming a positive feedback loop.
[0060] Ti3C2T doped in the drug-loaded layer X MXene nanosheets, with a diameter of 200 nm-2 μm and a thickness of 1-5 nm, have a two-dimensional sheet structure. Unlike traditional zero-dimensional nanoparticles (such as nano-silver and nano-silica) that easily clog the pores between fibers, the two-dimensional sheet structure of MXene forms surface-to-point contact in nanofibers and does not block the gas transport channels between fibers. On the contrary, MXene nanosheets form gas sliding channels on the fiber surface, allowing water vapor molecules to pass through the fiber membrane with lower resistance.
[0061] MXene Ti3C2T X With excellent photothermal conversion efficiency, MXene nanosheets efficiently convert light energy into heat energy under near-infrared light irradiation, generating local high temperatures and physically killing bacteria through thermal effects. Unlike traditional antibiotics or metal ion antibacterial agents, MXene's photothermal antibacterial mechanism is a physical sterilization mechanism that does not rely on drug release or reactive oxygen species generation, and therefore does not induce drug resistance in bacteria.
[0062] The metal-phenolic network itself has broad-spectrum antibacterial activity (by disrupting bacterial cell membranes and generating reactive oxygen species), which, together with the photothermal antibacterial properties of MXene, forms a dual antibacterial barrier of chemical and physical antibacterial action, achieving synergistic antibacterial action without antibiotics or drug resistance.
[0063] The wet adhesion function of the metal-phenolic network, the one-way moisture conduction function of the Janus wetting gradient adhesion layer, the photothermal antibacterial function of MXene, and the on-demand thermotherapy function of liquid metal form a four-fold linkage mechanism of "adhesion, moisture conduction, antibacterial and thermotherapy". The metal-phenolic network firmly adheres the bandage to the moist wound, the Janus layer continuously drains the wound exudate outward, MXene sterilizes under light when flowing through the drug-loaded layer, the liquid metal generates Joule heating under the alternating magnetic field to promote tissue regeneration, and polyrotaxane ensures the elastic recovery of the bandage.
[0064] Example 2
[0065] The purpose of this embodiment is to provide a method for preparing a composite nanofiber elastic adhesive bandage, including the following steps:
[0066] Step 1: Preparation of spinning solution
[0067] A metal-phenolic network modified Janus hydrophilic layer spinning solution A was prepared by dissolving hydrophilic polymer materials, phenolic ligands, and metal ions in a solvent; a Janus hydrophobic layer spinning solution B was prepared by dissolving hydrophobic polymer materials in a solvent; a drug-loaded layer spinning solution C was prepared by mixing and dispersing hydrophilic polymer materials and MXene nanosheets in a solvent; a liquid metal-piezoelectric elastic layer spinning solution D was prepared by mixing and dispersing liquid metal nanodroplets, piezoelectric polymers, and elastic polymers in a solvent; and a polyrotaxane breathable layer spinning solution E was prepared by mixing polyrotaxane slip ring elastomers and thermoplastic elastomers in a solvent.
[0068] Step 2: Setting up the electrospinning device
[0069] The electrospinning device includes a high-voltage power supply, a liquid supply mechanism, a spinning nozzle, and a collecting electrode. The collecting electrode includes a conductive layer, a first elastic membrane, and a second elastic membrane stacked sequentially from bottom to top. Both the first and second elastic membranes are insulating materials and are under tension. The tension of the first elastic membrane is greater than that of the second elastic membrane. Multiple strip-shaped grooves are uniformly arranged on the first elastic membrane along its tension direction. Circular through holes are uniformly distributed on the second elastic membrane.
[0070] It should be noted that the high-voltage power supply, liquid supply mechanism and spinning nozzle are all existing technologies. Their detailed structures can be found in existing literature and journals, and they can also be purchased directly on the market, or the parts can be purchased on the market and assembled, etc. They are not what this invention is meant to protect, and will not be described in detail here, nor are they shown in the accompanying drawings.
[0071] Step 3: Electrospun metal-phenolic network modified Janus wetting gradient adhesion layer
[0072] The metal-phenolic network modified Janus hydrophilic layer spinning solution A is injected into the liquid supply mechanism, and the metal-phenolic network modified hydrophilic inner layer is electrospun on the second elastic membrane; then switch to the Janus hydrophobic layer spinning solution B, and directly electrospun the hydrophobic outer layer on the hydrophilic inner layer to form an electrospun metal-phenolic network modified Janus wetting gradient adhesion layer.
[0073] Step 4: Electrospinning the drug-loaded layer
[0074] The drug-coating solution C is injected into the supply mechanism, and a nanofiber film doped with MXene nanosheets is directly electrospun on the surface of the metal-phenolic network modified Janus wetting gradient adhesion layer as a drug-carrying layer.
[0075] Step 5: Electrospinning liquid metal-piezoelectric elastic layer
[0076] The liquid metal-piezoelectric elastic layer spinning solution D is injected into the liquid supply mechanism, and a layer of liquid metal nanodroplets, piezoelectric polymer and elastic polymer composite nanofiber film is directly electrospun on the upper surface of the drug-loaded layer as the liquid metal-piezoelectric elastic layer, and the liquid metal-piezoelectric elastic layer is polarized.
[0077] Step 6: Electrospun polyrotaxane breathable layer
[0078] The polyrotaxane permeable layer spinning solution E is injected into the liquid supply mechanism, and a polyrotaxane slip ring elastomer and thermoplastic elastomer composite nanofiber membrane is directly electrospun on the upper surface of the liquid metal-piezoelectric elastic layer as the polyrotaxane permeable layer.
[0079] Step 7: Take the membrane
[0080] The second elastic membrane and the first elastic membrane are restored to their original lengths, and the resulting multilayer composite nanofiber membrane shrinks to form a double-folded structure. The multilayer composite nanofiber membrane is then removed from the second elastic membrane to obtain the composite nanofiber elastic adhesive bandage.
[0081] Furthermore, in step one:
[0082] The spinning solution A for the metal-phenolic network modified Janus hydrophilic layer is prepared by adding 0.4-0.8 g chitosan, 0.2-0.5 g polyvinyl alcohol, 0.01-0.05 g tannic acid, and 0.002-0.015 g FeCl3·6H2O to 8-12 mL of distilled water and stirring at room temperature to dissolve the mixture. The tannic acid reacts with the FeCl3·6H2O. 3+ Prepared by in-situ coordination to form a metal-phenolic network;
[0083] Janus hydrophobic spinning solution B is prepared by adding 0.3-0.6 g of polylactic acid or polycaprolactone to 6-10 mL of a mixed solvent of chloroform and methanol, and stirring at room temperature to dissolve it.
[0084] The spinning solution C for the drug-loaded layer consists of 0.4-0.8 g chitosan, 0.01-0.05 g polyethylene oxide, and 0.005-0.05 g MXene Ti3C2T. X Nanosheets were prepared by adding 8-12 mL of solvent, ultrasonically dispersing, and then stirring at room temperature.
[0085] The liquid metal-piezoelectric elastic layer spinning solution D is prepared by dispersing 0.01-0.1 g of eutectic gallium indium alloy nanodroplets in 6-10 mL of N,N-dimethylformamide solution containing 0.3-0.6 g of polyvinylidene fluoride and 0.2-0.5 g of thermoplastic polyurethane, followed by ultrasonic dispersion and stirring at 40-60℃ to dissolve.
[0086] The polyrotaxane breathable layer spinning solution E is prepared by adding 0.05-0.2 g of α-cyclodextrin-polyethylene glycol polyrotaxane and 0.5-1.0 g of thermoplastic polyurethane to 8-12 mL of N,N-dimethylformamide solution and stirring at room temperature to dissolve.
[0087] Furthermore, in step two, the pre-stretch rate of the first elastic membrane is 80-120%, and the pre-stretch rate of the second elastic membrane is 20-50%; the groove width of the strip groove of the first elastic membrane in the unstretched state is 0.5-mm; the diameter of the circular through hole of the second elastic membrane in the unstretched state is 3-8 mm, and the groove width of the strip groove is smaller than the diameter of the circular through hole.
[0088] Furthermore, in step three, the spinning parameters for the electrospun metal-phenolic network modified Janus wetting gradient adhesion layer are as follows: for the hydrophilic inner layer, the spinning voltage is 10-15 kV and the receiving distance is 10-15 cm; for the hydrophobic outer layer, the spinning voltage is 15-20 kV and the receiving distance is 15-20 cm.
[0089] Furthermore, the polarization parameters in step five are: polarization electric field strength 50-150 kV / cm, polarization temperature 80-120℃, and polarization time 30-120 min.
[0090] Experimental methods
[0091] (1) Elastic recovery rate test – based on YY / T 0507-2009 "Characteristics and test methods for basic performance parameters of medical elastic bandages"
[0092] A horizontal tensile testing instrument was used to apply a working tensile force at a tensile rate of 200-500 mm / min, and the recovery length of the bandage after the working tensile force was removed was measured.
[0093] Sample grouping:
[0094] Control group 1: A three-layer composite nanofiber elastic bandage was prepared using the method described in Chinese patent CN201911197939.0.
[0095] Control group 2: Commercially available medical elastic bandages;
[0096] Experimental Group 1: The four-layer composite nanofiber elastic adhesive bandage of the present invention (containing polyrotaxane + double pleats)
[0097] Experimental Group 2: The four-layer composite nanofiber elastic adhesive bandage of the present invention (containing polyrotaxane + liquid metal + double pleats)
[0098] (2) Air permeability test—based on GB / T 12704 and YY / T 0471.2-2004
[0099] The mass of water vapor passing through a unit area sample was determined by the permeation cup weighing method under conditions of 38℃ and 90% relative humidity over 24 hours.
[0100] (3) Adhesion test—According to YY / T 0148-2006 "General Requirements for Medical Tape"
[0101] Peel strength was tested under both dry and wet conditions (skin simulant moistened with physiological saline).
[0102] (4) Antibacterial performance test—based on GB / T 20944 (inhibition zone method)
[0103] The antibacterial activity of the samples against Staphylococcus aureus (ATCC 6538) was tested using the inhibition zone method.
[0104] For detailed experimental results, please refer to Table 1;
[0105] Table 1. Test results of elastic recovery rate (based on YY / T 0507-2009)
[0106] Test Project Control group 1 Control group 2 Experimental group 1 Experimental group 2 Maximum elongation 1050% 180-350% 1250% 1320% 100-cycle recovery rate 88.6% 72.3% 97.2% 98.1% 500-cycle response rate 72.4% 58.1% 93.5% 95.2% 1000-cycle response rate Not up to standard 42.6% 88.4% 91.7% Stratification phenomenon (after 1000 cycles) Clearly layered - No layering No layering
[0107] Through Table 1 and Figure 1 It can be seen that the recovery rate of experimental group 2 reached 91.7% after 1000 cycles, which was significantly improved compared with control group 1 (72.4% after 500 cycles); the pulley effect of polyrotaxane effectively dispersed the interlayer stress and solved the delamination problem.
[0108] The sliding energy dissipation of polyrotaxane slip ring elastomer at the molecular scale and the unfolding-recovery of the double-folded structure at the mesoscale form a cross-scale elastic response, which improves fatigue life by more than 10 times.
[0109] Table 2. Results of air permeability test (based on GB / T 12704 / YY / T 0471.2)
[0110] Test Project Control group 1 Control group 2 Experimental group 1 Experimental group 2 <![CDATA[Water vapor transmission rate (g / m 2 ·24h)]]> 2850 620 11200 13500 Static air permeability (mm / s) 85 32 189 235 Change in air permeability when stretched by 50% -12% -25% +22% +35% <![CDATA[Unidirectional moisture conductivity (mL / min·cm 2 )]]> none none 3.8 4.7
[0111] Through Table 2, Figure 2 and Figure 3 It can be seen that the water vapor transmission rate of experimental group 2 reached 13500 g / m. 2 • 24h, compared with control group 1 (2850), it increased by 374% and compared with the commercially available bandage of control group 2 (620), it increased by 2077%.
[0112] The air permeability of experimental group 2 increased by 35% when stretched by 50% (compared to a decrease of 12-25% in the control group), which is attributed to the formation of additional nanopores due to interfacial debonding of eutectic gallium indium alloy droplets during stretching.
[0113] MXene's two-dimensional sheet-like structure forms gas sliding channels on the fiber surface, further enhancing its breathability.
[0114] Table 3. Adhesion test results (based on YY / T 0148-2006)
[0115] Test Project Control group 1 Control group 2 Experimental group 1 Experimental group 2 Dry peel strength (N / cm) 1.2 2.8 5.8 7.2 Wet peel strength (N / cm) 0.3 1.6 5.2 6.8 Retention rate in wet and dry states 25% 57% 90% 94%
[0116] Through Table 3 and Figure 4 It can be seen that the wet peel strength of experimental group 2 reached 6.8 N / cm, which was 2167% higher than that of control group 1 (0.3), exceeding the YY / T 0148-2006 standard (≥1.0 N / cm) by 580%.
[0117] In the metal-phenolic network, the catechol groups form more hydrogen bonds and coordination bonds with skin surface proteins in a humid environment, achieving a wet / dry state retention rate of 94%, which completely solves the problem of traditional bandage adhesion failure in a wet state.
[0118] The Janus structure's one-way moisture-wicking function continuously removes interfacial moisture, ensuring that the metal-phenolic network adhesion layer always maintains optimal contact.
[0119] Table 4. Antibacterial performance test results (based on GB / T 20944)
[0120] Test Project Control group 1 Control group 2 Experimental group 1 Experimental group 2 Inhibition zone against Staphylococcus aureus (mm) 9.2 0 22.5 28.7 Incremental rate of inhibition zone after near-infrared light irradiation +5% - +68% +85%
[0121] As shown in Table 3, the introduction of MXene significantly increased the inhibition zone from 9.2 mm to 28.7 mm, an increase of 212%.
[0122] The inhibition zone increased by 85% after near-infrared light irradiation, confirming the photothermal antibacterial mechanism of MXene, which physically kills bacteria through photothermal effect and avoids drug resistance problems.
[0123] The metal-phenolic network itself has broad-spectrum antibacterial activity (by disrupting bacterial cell membranes) and forms a dual antibacterial barrier with MXene.
[0124] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A composite nanofiber elastic adhesive bandage, characterized in that, Including those arranged in layers from bottom to top: Metal-phenolic network modified Janus wetting gradient adhesion layer; Drug-carrying layer doped with MXene two-dimensional nanosheets; Liquid metal-elastomer composite piezoelectric elastic layer; Polyrotaxane slip ring elastomer reinforces the breathable layer; The metal-phenolic network modified Janus wetting gradient adhesion layer, drug-loaded layer, liquid metal-elastomer composite piezoelectric elastic layer, and polyrotaxane slip ring elastomer reinforced breathable layer all have a double-folded structure. The metal-phenolic network modified Janus wetting gradient adhesion layer has asymmetric wettability, with an inner layer contact angle of less than 60 degrees and an outer layer contact angle of greater than 130 degrees. The inner layer is doped with a metal-phenolic network. The metal-phenolic network of the metal-phenolic network modified Janus wetting gradient adhesion layer is formed by the self-assembly of phenolic ligands and metal ions. The liquid metal-elastomer composite piezoelectric elastic layer is made by electrospinning liquid metal nanodroplets and piezoelectric polymer; the polyrotaxane slip ring elastomer reinforced breathable layer is made by electrospinning polyrotaxane slip ring elastomer and thermoplastic elastomer, wherein the polyrotaxane used in the polyrotaxane slip ring elastomer is formed by cyclic molecules threaded onto polymer chains.
2. The composite nanofiber elastic adhesive bandage according to claim 1, characterized in that, The MXene two-dimensional nanosheets are Ti3C2T X Transition metal carbide nanosheets; Ti3C2T X The transition metal carbide nanosheets have a diameter of 200 nm-2 μm and a thickness of 1-5 nm, with a doping mass of 0.5-5 wt% in the drug-loaded layer; MXene two-dimensional nanosheets generate a photothermal effect under visible or near-infrared light irradiation, and can be used for on-demand antibacterial applications.
3. The composite nanofiber elastic adhesive bandage according to claim 1, characterized in that, The phenolic ligands in the metal-phenolic network are tannic acid or gallic acid, and the metal ion in the metal-phenolic network is Fe. 3+ or Cu 2+ The molar ratio of phenolic ligands to metal ions is 1-3:1; the doping mass of the metal-phenolic network in the metal-phenolic network modified Janus wetting gradient adhesion layer is 2-10 wt%.
4. The composite nanofiber elastic adhesive bandage according to claim 1, characterized in that, The liquid metal is a eutectic gallium-indium alloy, in which the gallium content is 75-76 wt% and the indium content is 24-25 wt%. The liquid metal nanodroplets have a particle size of 50-200 nm. After being modified with surface ligands, the liquid metal nanodroplets are dispersed in the piezoelectric polymer matrix constituting the liquid metal-elastomer composite piezoelectric elastic layer. The mass percentage of the liquid metal nanodroplets in the fiber formed by the composite piezoelectric elastic layer is 1-10 wt%.
5. The composite nanofiber elastic adhesive bandage according to claim 1, characterized in that, The polyrotaxane is formed by α-cyclodextrin cyclic molecules threaded onto a polyethylene glycol polymer chain; wherein the molar ratio of α-cyclodextrin to the repeating ethylene glycol unit in the polyethylene glycol chain is 1:2-4; and the blending mass percentage of polyrotaxane in the polyrotaxane slip ring elastomer reinforced breathable layer is 5-20 wt%.
6. A method for preparing a composite nanofiber elastic adhesive bandage according to any one of claims 1-5, characterized in that, Includes the following steps: Step 1: Preparation of spinning solution A metal-phenolic network modified Janus hydrophilic layer spinning solution A was prepared by dissolving hydrophilic polymer materials, phenolic ligands, and metal ions in a solvent; a Janus hydrophobic layer spinning solution B was prepared by dissolving hydrophobic polymer materials in a solvent; a drug-loaded layer spinning solution C was prepared by mixing and dispersing hydrophilic polymer materials and MXene nanosheets in a solvent; a liquid metal-piezoelectric elastic layer spinning solution D was prepared by mixing and dispersing liquid metal nanodroplets, piezoelectric polymers, and elastic polymers in a solvent; and a polyrotaxane breathable layer spinning solution E was prepared by mixing polyrotaxane slip ring elastomers and thermoplastic elastomers in a solvent. Step 2: Setting up the electrospinning device The electrospinning device includes a high-voltage power supply, a liquid supply mechanism, a spinning nozzle, and a collecting electrode. The collecting electrode includes a conductive layer, a first elastic membrane, and a second elastic membrane stacked sequentially from bottom to top. Both the first and second elastic membranes are insulating materials and are under tension. The tension of the first elastic membrane is greater than that of the second elastic membrane. Multiple strip-shaped grooves are uniformly arranged on the first elastic membrane along its tension direction. Circular through holes are uniformly distributed on the second elastic membrane. Step 3: Electrospun metal-phenolic network modified Janus wetting gradient adhesion layer The metal-phenolic network modified Janus hydrophilic layer spinning solution A is injected into the liquid supply mechanism, and the metal-phenolic network modified hydrophilic inner layer is electrospun on the second elastic membrane; then switch to the Janus hydrophobic layer spinning solution B, and directly electrospun the hydrophobic outer layer on the hydrophilic inner layer to form an electrospun metal-phenolic network modified Janus wetting gradient adhesion layer. Step 4: Electrospinning the drug-loaded layer The drug-coating solution C is injected into the supply mechanism, and a nanofiber film doped with MXene nanosheets is directly electrospun on the surface of the metal-phenolic network modified Janus wetting gradient adhesion layer as a drug-carrying layer. Step 5: Electrospinning liquid metal-piezoelectric elastic layer The liquid metal-piezoelectric elastic layer spinning solution D is injected into the liquid supply mechanism, and a layer of liquid metal nanodroplets, piezoelectric polymer and elastic polymer composite nanofiber film is directly electrospun on the upper surface of the drug-loaded layer as the liquid metal-piezoelectric elastic layer, and the liquid metal-piezoelectric elastic layer is polarized. Step 6: Electrospun polyrotaxane breathable layer The polyrotaxane permeable layer spinning solution E is injected into the liquid supply mechanism, and a polyrotaxane slip ring elastomer and thermoplastic elastomer composite nanofiber membrane is directly electrospun on the upper surface of the liquid metal-piezoelectric elastic layer as the polyrotaxane permeable layer. Step 7: Take the membrane The second elastic membrane and the first elastic membrane are restored to their original lengths, and the resulting multilayer composite nanofiber membrane shrinks to form a double-folded structure. The multilayer composite nanofiber membrane is then removed from the second elastic membrane to obtain the composite nanofiber elastic adhesive bandage.
7. The method for preparing the composite nanofiber elastic adhesive bandage according to claim 6, characterized in that, In step one: The spinning solution A for the metal-phenolic network modified Janus hydrophilic layer is prepared by adding 0.4-0.8 g chitosan, 0.2-0.5 g polyvinyl alcohol, 0.01-0.05 g tannic acid, and 0.002-0.015 g FeCl3·6H2O to 8-12 mL of distilled water and stirring at room temperature to dissolve the mixture. The tannic acid reacts with the FeCl3·6H2O. 3+ Prepared by in-situ coordination to form a metal-phenolic network; Janus hydrophobic spinning solution B is prepared by adding 0.3-0.6 g of polylactic acid or polycaprolactone to 6-10 mL of a mixed solvent of chloroform and methanol, and stirring at room temperature to dissolve it. The spinning solution C for the drug-loaded layer consists of 0.4-0.8 g chitosan, 0.01-0.05 g polyethylene oxide, and 0.005-0.05 g MXeneTi3C2T. X Nanosheets were prepared by adding 8-12 mL of solvent, ultrasonically dispersing, and then stirring at room temperature. The liquid metal-piezoelectric elastic layer spinning solution D is prepared by dispersing 0.01-0.1 g of eutectic gallium indium alloy nanodroplets in 6-10 mL of N,N-dimethylformamide solution containing 0.3-0.6 g of polyvinylidene fluoride and 0.2-0.5 g of thermoplastic polyurethane, followed by ultrasonic dispersion and stirring at 40-60℃ to dissolve. The polyrotaxane breathable layer spinning solution E is prepared by adding 0.05-0.2 g of α-cyclodextrin-polyethylene glycol polyrotaxane and 0.5-1.0 g of thermoplastic polyurethane to 8-12 mL of N,N-dimethylformamide solution and stirring at room temperature to dissolve.
8. The method for preparing the composite nanofiber elastic adhesive bandage according to claim 6, characterized in that, In step two, the pre-stretch rate of the first elastic membrane is 80-120%, and the pre-stretch rate of the second elastic membrane is 20-50%. The groove width of the strip groove of the first elastic membrane in the unstretched state is 0.5-mm. The diameter of the circular through hole of the second elastic membrane in the unstretched state is 3-8 mm, and the groove width of the strip groove is smaller than the diameter of the circular through hole.
9. The method for preparing the composite nanofiber elastic adhesive bandage according to claim 6, characterized in that, In step three, the spinning parameters for the electrospun metal-phenolic network modified Janus wetting gradient adhesion layer are as follows: for the hydrophilic inner layer, the spinning voltage is 10-15 kV and the receiving distance is 10-15 cm; for the hydrophobic outer layer, the spinning voltage is 15-20 kV and the receiving distance is 15-20 cm.
10. The method for preparing the composite nanofiber elastic adhesive bandage according to claim 6, characterized in that, The parameters for polarization treatment in step five are: polarization electric field strength 50-150 kV / cm, polarization temperature 80-120℃, and polarization time 30-120 min.
Citation Information
Patent Citations
Composite nanofiber elastic bandage and its preparation method
CN110841102B